The role of peer-assisted learning in enhancing the learning of undergraduate nursing students in clinical practice: a qualitative systematic review protocol - Carey, M.; Kent, B.; Latour, Jos (University of Adelaide * Faculty of Health Sciences, 2016)
Review question/objective: The objective of this qualitative systematic review is to identify and synthesize the best available evidence on experiences of peer teaching and learning among student nurses in the clinical environment. The specific objectives are: To identify nursing students’ experiences of peer-assisted learning (PAL) and teaching within the clinical setting. To identify qualitative data that highlight the strengths and weaknesses of PAL among student nurses in clinical settings. To explore whether PAL enhances the competence of student nurses’ learning in clinical settings.